2020
DOI: 10.1186/s13148-020-00906-5
|View full text |Cite
|
Sign up to set email alerts
|

Circulating unmethylated CHTOP and INS DNA fragments provide evidence of possible islet cell death in youth with obesity and diabetes

Abstract: Background: Identification of islet β cell death prior to the onset of type 1 diabetes (T1D) or type 2 diabetes (T2D) might allow for interventions to protect β cells and reduce diabetes risk. Circulating unmethylated DNA fragments arising from the human INS gene have been proposed as biomarkers of β cell death, but this gene alone may not be sufficiently specific to report β cell death. Results: To identify new candidate genes whose CpG sites may show greater specificity for β cells, we performed unbiased DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 39 publications
0
17
1
Order By: Relevance
“…Using banked sera from subjects in the T1D Exchange registry, one study demonstrated elevations in both unmethylated INS and methylated INS in subjects from both C-peptide-positive and C-peptide-negative subjects with longstanding (≥9 years) T1D [ 37 ]. These findings seem indicative of the persistence of β cells in such subjects, where ongoing β-cell death may give rise to circulating unmethylated INS signals and ongoing systemic autoimmunity/inflammation may give rise to elevated methylated INS signals [ 38 ]. At least two studies have examined the occurrence of β-cell death in subjects at risk for T1D.…”
Section: Development Of Dna-based Biomarkers Of β-Cell Deathmentioning
confidence: 99%
See 3 more Smart Citations
“…Using banked sera from subjects in the T1D Exchange registry, one study demonstrated elevations in both unmethylated INS and methylated INS in subjects from both C-peptide-positive and C-peptide-negative subjects with longstanding (≥9 years) T1D [ 37 ]. These findings seem indicative of the persistence of β cells in such subjects, where ongoing β-cell death may give rise to circulating unmethylated INS signals and ongoing systemic autoimmunity/inflammation may give rise to elevated methylated INS signals [ 38 ]. At least two studies have examined the occurrence of β-cell death in subjects at risk for T1D.…”
Section: Development Of Dna-based Biomarkers Of β-Cell Deathmentioning
confidence: 99%
“…A more recent study [ 38 ] examined autoantibody-negative first-degree relatives of those with T1D (a group that is at modestly higher risk of developing T1D compared to otherwise healthy controls) and demonstrated striking elevations of unmethylated INS in this group. Although the findings of these studies suggest that a pre-symptomatic period with active β-cell death may occur, these findings were not corroborated in another study that used a DNA sequencing approach to examine unmethylated INS in subjects at-risk for T1D [ 29 ].…”
Section: Development Of Dna-based Biomarkers Of β-Cell Deathmentioning
confidence: 99%
See 2 more Smart Citations
“…The study suggested that the methylation changes in the circulating blood cells could serve as a biomarker for prediction of metabolic diseases in offsprings of women with obesity and GDM ( Hjort et al, 2018 ). A different study identified the differential methylation status of circulating cell-free CHTOP and INS1 DNA fragments as potential biomarkers for possible islet death in youths with obesity and diabetes ( Syed et al, 2020 ). A study by Nishimoto et al investigated the role of cfDNA in development adipose tissue inflammation.…”
Section: Therapeutic Strategies For Obesity Treatmentmentioning
confidence: 99%